2023
DOI: 10.21203/rs.3.rs-2628492/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Access to Care and Therapy for Kawasaki Disease in the Arab Countries: A Kawasaki Disease Arab Initiative (Kawarabi) Multicenter Survey:

Abstract: Kawasaki Disease (KD) is still the most common acquired heart disease in children below the age of five years; it has been well described in the developed world; however, data from the Arab world are limited to case reports or single-center case series. In an effort of optimizing KD research in the Arab world, a group of physicians and researchers established the KD Arab Initiative (Kawarabi) in 2021, and published the first survey, which showed disparities in the availability of intravenous immunoglobulin (IV… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…13 The second article published in May 2023 showed that ease of access to care favored large and mid-size cities over rural areas in almost half of the surveyed member countries of Kawarabi . 14 Four virtual educational webinars moderated by national and international leaders in the field of KD have been held to address the epidemiology of KD and MIS-C in various Arab countries and were well attended by approximately 100 participants per webinar.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…13 The second article published in May 2023 showed that ease of access to care favored large and mid-size cities over rural areas in almost half of the surveyed member countries of Kawarabi . 14 Four virtual educational webinars moderated by national and international leaders in the field of KD have been held to address the epidemiology of KD and MIS-C in various Arab countries and were well attended by approximately 100 participants per webinar.…”
Section: Resultsmentioning
confidence: 99%
“…There are significant practice variations in the management of KD, a low level of awareness of the disease in the general population, and access to care favors large to mid-size cities over rural areas in close to half of the participating countries. 13,14 Ease of access to IVIG differs between institutions. 13 The lack of readily available IVIG combined with low awareness of the disease in the general population can potentially lead to underdiagnosis, delay treatment, and subsequently increase the risk of coronary artery aneurysms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation